Bridging aero-fracture evolution with the characteristics of the acoustic emissions in a porous medium - Turkaya, Semih; Toussaint, Renaud; Eriksen, Fredrik K.; Zecevic, Megan; Daniel, Guillaume; Flekkøy, Eirik G.; Måløy, Knut Jørgen (Frontiers in Physics, 2015)
The characterization and understanding of rock deformation processes due to fluid flow is a challenging problem with numerous applications. The signature of this problem can be found in Earth Science and Physics, notably with applications in natural hazard understanding, mitigation or forecast (e.g. earthquakes, landslides with hydrological control, volcanic eruptions), or in industrial applications such as hydraulic-fracturing, steam-assisted gravity drainage, CO₂ sequestration operations or soil remediation. Here we investigate the link between the visual deformation and the mechanical wave signals generated due to fluid injection into porous media. In a rectangular Hele-Shaw Cell, side air injection causes burst movement and compaction of grains along with channeling (creation of high permeability channels empty of grains). During the initial compaction and emergence of the main channel, the hydraulic fracturing in the medium generates a large non-impulsive low frequency signal in the frequency range 100 Hz - 10 kHz. When the channel network is established, the relaxation of the surrounding medium causes impulsive aftershock-like events, with high frequency (above 10 kHz) acoustic emissions, the rate of which follows an Omori Law. These signals and observations are comparable to seismicity induced by fluid injection. Compared to the data obtained during hydraulic fracturing operations, low frequency seismicity with evolving spectral characteristics have also been observed. An Omori-like decay of microearthquake rates is also often observed after injection shut-in, with a similar exponent p≃0.5 as observed here, where the decay rate of aftershock follows a scaling law dN/dt ∝(t-t₀ )-p . The physical basis for this modified Omori law is explained by pore pressure diffusion affecting the stress relaxation.